2018
DOI: 10.3389/fnbot.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Developing Hierarchical Schemas and Building Schema Chains Through Practice Play Behavior

Abstract: Examining the different stages of learning through play in humans during early life has been a topic of interest for various scholars. Play evolves from practice to symbolic and then later to play with rules. During practice play, infants go through a process of developing knowledge while they interact with the surrounding objects, facilitating the creation of new knowledge about objects and object related behaviors. Such knowledge is used to form schemas in which the manifestation of sensorimotor experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…The aforementioned works deal with the development of high-level action sequences that allow a robotic agent to solve complex manipulation problems. Here, we describe a novel chaining mechanisms of Dev-PSchema; a open-ended learning tool based on PSchema (which was firstly introduced in [25] and [26]) to extend its problem-solving capability. It is designed to discover a set of possible solutions capable of achieving the desired target state of a given problem through artificial play.…”
Section: Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned works deal with the development of high-level action sequences that allow a robotic agent to solve complex manipulation problems. Here, we describe a novel chaining mechanisms of Dev-PSchema; a open-ended learning tool based on PSchema (which was firstly introduced in [25] and [26]) to extend its problem-solving capability. It is designed to discover a set of possible solutions capable of achieving the desired target state of a given problem through artificial play.…”
Section: Related Studiesmentioning
confidence: 99%
“…It includes the number of times an object has appeared in the environment (similarity S), the number of times it has been used in schemas (novelty N ), and the success rate and frequency of use of those schemas in memory (habituation H). These concepts are fully described in [25] and modelled as shown in the supplementary material.…”
Section: B Schema Excitation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary and secondary circular reactions clearly encompass the above-mentioned intuitive notion of (simple, basic, stereotyped) “sensorimotor associations.” They are subsequently hierarchically organized in action schemes thanks to assimilation, accommodation and organisation. Action schemes corresponding to more complex, high-level, goal-directed actions can be decomposed into finer-grained action schemes, and, in the end, into their constituent circular reactions (this idea already appears in, e.g., von Glasersfeld, 1995 ; Kumar et al, 2018 ). For instance, “reaching for and grasping a cup of tea” can be decomposed into simpler actions schemes, e.g., “focus on the cup,” “stretch the arm,” “pre-shape the hand,” etc.…”
Section: On the Purpose Of Assistive Systemsmentioning
confidence: 99%
“…By combining cognitive psychology and robotics, [7][8] revealed a psychological structure with schema and chain for robots to learn simple tasks. These studies showed good effect on the application of higher-level cognitive strategies for robots.…”
Section: Introductionmentioning
confidence: 99%